Public education, multinational citizenship, and territorial legitimacy: analyzing the 2004 and 2023 Ontario curricula on Indigenous peoples - Luoma, Michael (Frontiers in Political Science, 2024)
Through an analysis of the Ontario public school curriculum grounded in normative analytics drawn from philosophical theories of territorial rights and state legitimacy, this paper investigates the role of public education in promoting and/or undermining the conditions for the formation of multinational identities among the members of the (English-speaking) majority group in Canada. That is, it investigates compulsory public education curricula for the potential to transmit representations that furnish students with the resources for forming beliefs and attitudes that recognize Canada to be a treaty federation of distinct peoples with rights to territory and self-determination. As the paper argues, under present conditions in the Canadian context, public education with a mind to producing a multinational ethos is a requirement of political legitimacy. As we will see, there is evidence to suggest that public education is undergoing a transformation in Canada’s largest province with respect to its treatment of contemporary Indigenous presence, historical treaty-making, and the history of colonial wrongdoing – although serious omissions remain, notably in the areas of Indigenous governance, and consent and consultation. The results of curricular evolution can thus be expected to remain ambiguous with respect to the ideals of territorial legitimacy and treaty federalism, alongside the problematic discursive arena provided by the national news media and other sites of identity formation.